Omnichannel Readiness of Hotel Distribution Systems in an Emerging Tourism Destination: Evidence from Labuan Bajo, Indonesia - Paul Hanny Wadhi; Fitri Ciptosari; Agus Wahyudi (Eastasouth Institute, 2026)
The rapid expansion of digital distribution channels has reshaped hotel marketing and booking practices, particularly in emerging tourism destinations. This study examines the omnichannel readiness of hotel distribution systems in Labuan Bajo, Indonesia, with the aim of understanding the extent of intermediary dependency, system integration, and destination-level implications. A qualitative case study approach was employed, combining analysis of hotel booking data with semi-structured interviews with hotel management. The study assessed distribution concentration, channel dependency, and the level of integration among key distribution systems using an interview-based readiness scoring framework. The findings reveal a high dependency on online travel platforms, with booking volumes concentrated among a small number of global intermediaries. Despite the presence of multiple digital channels, the results indicate limited omnichannel readiness due to fragmented system integration, resulting in inconsistent customer experience management. The study further demonstrates that limited omnichannel readiness is not only a firm-level challenge but also a destination development issue, as fragmented hotel distribution systems may undermine experience consistency and destination competitiveness. This research contributes to tourism and hospitality literature by providing empirical evidence from an emerging tourism destination and by reframing omnichannel readiness as a form of soft infrastructure within destination development. The findings offer practical insights for hotel operators, destination management organizations, and policymakers seeking to strengthen digital distribution capabilities and support sustainable tourism development in emerging destinations.